2015
DOI: 10.1158/1078-0432.ccr-14-2696
|View full text |Cite
|
Sign up to set email alerts
|

CD47 EnhancesIn VivoFunctionality of Artificial Antigen-Presenting Cells

Abstract: Purpose Artificial Antigen-Presenting Cells, aAPC, have successfully been used to stimulate antigen-specific T cell responses in vitro as well as in vivo. While aAPC compare favorable to autologous dendritic cells in vitro, their effect in vivo might be diminished through rapid clearance by macrophages. Therefore, to prevent uptake and minimize clearance of aAPC by macrophages, and thereby increasing in vivo functionality, we investigated the efficiency of “don’t eat me” three-signal aAPC compared to classical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
1
14
1
Order By: Relevance
“…In the nonspecific cytolysis controls, SPCs from all groups showed ,11% of baseline cytolysis against SP2/0 cells (Figure 11). Different from the previous studies of SaAPCs, 10,16 CD47-modified SaAPCs, 30 and SaAPCs, 28 the present study initially illustrated the EaAPC PEG and EaAPC PEG/CD47 . The results from in vivo experiments demonstrated that the superimposed or synergistic effects of ellipsoidal stretch, PEGylation, and self-marker CD47 conjugation onto nano-aAPC tailored much stronger in vivo functionality of the EaAPC PEG/CD47 to expand antigen-specific CTLs, facilitate their local infiltration, and eventually inhibit tumor growth, when compared to the control aAPCs with a function order Figure 8 eaaPc Peg/cD47 markedly augmented melanoma antigen-specific CTL responses in melanoma-bearing mice.…”
Section: Resultscontrasting
confidence: 76%
See 1 more Smart Citation
“…In the nonspecific cytolysis controls, SPCs from all groups showed ,11% of baseline cytolysis against SP2/0 cells (Figure 11). Different from the previous studies of SaAPCs, 10,16 CD47-modified SaAPCs, 30 and SaAPCs, 28 the present study initially illustrated the EaAPC PEG and EaAPC PEG/CD47 . The results from in vivo experiments demonstrated that the superimposed or synergistic effects of ellipsoidal stretch, PEGylation, and self-marker CD47 conjugation onto nano-aAPC tailored much stronger in vivo functionality of the EaAPC PEG/CD47 to expand antigen-specific CTLs, facilitate their local infiltration, and eventually inhibit tumor growth, when compared to the control aAPCs with a function order Figure 8 eaaPc Peg/cD47 markedly augmented melanoma antigen-specific CTL responses in melanoma-bearing mice.…”
Section: Resultscontrasting
confidence: 76%
“…28,29 Meanwhile, the CD47-conjugated spherical nano-aAPCs have also been developed with the enhanced effects of anti-phagocytosis and tumor inhibition. 30 In this study, PEGylation, CD47 conjugation, and ellipsoidal stretch were integrated into the generation of new "stealth" nano-aAPCs with microscale contact surface to minimize internalization and augment anti-tumor CTL responses in melanoma-bearing mice. PLGA, a biocompatible, biodegradable, and nontoxic polymer widely used in drug and vaccine delivery systems in human, [31][32][33] was employed to fabricate the spherical NPs and then was further stretched to the ellipsoidal NPs, followed by surface modification with PEGylation and surface co-coupling with H-2K b /TRP2 180-188 -Ig dimers, anti-CD28, and CD47-Fc.…”
Section: Introductionmentioning
confidence: 99%
“…The results are also in agreement with the finding from Bruns et al that CD47 increased the penetration and retention of PLGA-NPs in the damaged brain, thus enhancing the in vivo functionality of artificial APCs. 58 Here, the 217 nm tNPs were decorated with CD47-Fc, which led to a longer retention time in vivo and much fewer co-localizations with macrophages and DCs than the CD47 − tNPs, implying that CD47 molecules onto tNPs may minimize the engulfment of tNPs by phagocytes as expected. But we cannot eliminate the possibility of endocytosis and phagocytosis occurring in vivo.…”
Section: Discussionsupporting
confidence: 50%
“…Similar results were seen when artificial antigen presenting cells, fabricated from epoxy beads were co-cultured with macrophages. 76 This study demonstrated that phagocytosis inhibition was CD47 concentration dependent. Additionally, it was shown that CD47 did not interfere with the ability to expand antigen-specific T cells.…”
Section: Examples Of Cd47-modified Biomaterials Cd47-modified Therapementioning
confidence: 70%